Strategi Pemasaran Digital Pada Perusahaan E-Commerce - Afrizal Muslim; Eva Oktavia (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The rapid advancement of information technology has transformed the global business landscape, driving a shift from traditional marketing to digital marketing. E-commerce companies face increasingly intense competition in attracting and retaining customers. This study aims to analyze the digital marketing strategies implemented by e-commerce companies, identify the most effective digital channels, and evaluate their impact on increasing sales and brand awareness. The research employed a qualitative descriptive method, with data collected through in-depth interviews, observations of digital platforms, and documentation. The findings indicate that the combination of Social Media Marketing (SMM), Search Engine Optimization (SEO), and Content Marketing makes the most significant contribution to website traffic and sales conversion. The study concludes that content personalization and regular data analysis are essential for optimizing the efficiency of digital marketing budgets.